Digitalisasi Administrasi dan Penguatan Literasi Digital sebagai Katalisator Pelayanan Publik yang Inovatif dan Berkelanjutan di Desa Beluk Kenek Kabupaten Sumenep - Deby Febriyan Eprilianto; Suci Megawati; Galih Wahyu Pradana; Yuyun Eka Kartika Sari; Mohamad Hermy Hibatulloh; Lisa Amelia Sari; Muh. Rizal Khoirudin; Astrella Vanindya Sheren (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to promote administrative digitalization and enhance digital literacy as a catalyst for innovative and sustainable public services in Beluk Kenek Village, Sumenep Regency. The village has faced several challenges, such as manual administrative processes that hinder service efficiency, low levels of digital literacy among government officials and residents, and a limited understanding of the long-term benefits of digitalization. To address these issues, the program was implemented in three stages: planning, execution, and evaluation. The planning stage included online meetings, problem identification, and mapping of administrative needs. During the execution stage, a prototype of the digital village website was developed, along with the preparation of training materials tailored to the needs of both officials and the community. The evaluation stage focused on assessing system usability, collecting feedback, and ensuring readiness for further implementation. Preliminary results indicate strong support and commitment from village officials, successful development of a digital village website prototype, and readiness for upcoming digital literacy training sessions. This initiative is expected to increase transparency in governance, improve the efficiency of administrative services, and encourage greater community participation in the digital era. Furthermore, the program can serve as a replicable model for other villages, contributing to broader rural digital transformation and sustainable community development.